Changes in selected cytokines, acute-phase proteins, gonadal hormones and reproductive organs of non-pregnant does challenged with Mannheimia haemolytica serotype A2 and its LPS endotoxin - Kamarulrizal, Mat Isa; Lim, Eric Teik Chung; Abdullah, Faez Firdaus Jesse; Paul, Bura Thlama; Nur Azhar, Amira; Mohd Lila, Mohd Azmi; Salleh, Annas; Abba, Yusuf; Shamsuddin, Mohd Shafarin (Springer Nature, 2022)
Previous investigations have revealed that lipopolysaccharide (LPS) endotoxin from certain Gram-negative bacteria could adversely affect the reproductive system of female animals. However, it is unknown whether LPS endotoxin of Mannheimia haemolytica serotype A2, the principal causative bacteria that cause pneumonic mannheimiosis in small ruminants, may also induce similar insidious effects. Therefore, this study aimed to investigate the effects of M. haemolytica serotype A2 and its LPS endotoxin on the responses of female gonadal hormones (progesterone and oestrogen), pro-inflammatory cytokines (interleukin-1β, interleukin-6), acute-phase proteins (haptoglobin and serum amyloid A) and cellular changes via histopathology study of female reproductive organs of the treatment does. Twelve clinically healthy, non-pregnant, crossbred does were randomly allocated into three equal groups. Group 1 was administered intranasally with 2 ml of sterile phosphate-buffered saline (PBS) and served as a negative control group. Group 2 was challenged intranasally with 2 ml of bacterial inoculum containing 109 colony-forming units (CFU)/ml of M. haemolytica serotype A2, while Group 3 was challenged intravenously with 2 ml of LPS endotoxin extracted from 109 CFU/ml of M. haemolytica serotype A2. Following that, blood samples were collected serially at pre-determined intervals for serological analyses. All does were euthanised 60 days post-challenges, and tissue samples from the ovaries, oviducts, uterine horns, uterine body, cervix and vagina were collected for histopathological study. The serological result revealed a significant increase (p < 0.05) in the mean concentrations of progesterone, oestrogen, interleukin-1β, interleukin-6, haptoglobin and serum amyloid A for both challenged groups. Histopathologically, all reproductive organs (except the cervix and vagina) from both challenged groups displayed significant cellular alterations (p < 0.05) characterised by haemorrhage and congestion, necrosis and degeneration, inflammatory cell infiltration and oedema. This study provides new information that elucidates the potential role of pneumonic mannheimiosis in the pathogenesis of female infertility amongst small ruminants.